Exogenous factors dictate the quality of relationship between franchisee and franchisor: A Malaysian franchising experience - Mohd Harif, Mohd Amy Azhar; Hoe, Chee Hee; Chin, Othman (2013)
Franchising has often been widely accepted as an effective way to conduct and expand businesses. However a franchise system does not guarantee success in business and depends on a good relationship between both parties namely, franchisor and franchisee.These franchise relationships are unique and differ from the conventional business operations which require mutual co-existence and symbiotic relationship. Nevertheless without a good understanding between franchisor and franchisee, this relationship may have disputes that may require legal action for resolution.The success and failure of any franchise business are closely related to both the franchisor and franchisee and to what extent can they fulfill their responsibilities in order to maintain the level of franchise relationship quality (FRQ).Even though previous empirical researchers had viewed FRQ as a major indicator for the success of franchising system, the literature review showed that there was a lack of such research in identifying the exogenous factors that determine the FRQ.Thus, this qualitative research was conducted to identify the exogenous factors that influence the FRQ between franchisee and franchisor.This process involved the integration between an existing literature reviews and industry practices which emphasized on the gaps to solve the problem statement.Semi-structured interviews were conducted in this research to answer the four (4) main issues, ten (10) dimensions of FRQ, fourteen (14) exogenous factors that influenced the FRQ had been identified.